Automatically Segregating Greedy and Malicious Internet Flows - Brustoloni, Jose; Chen, Shuo (Proceedings of IEEE International Conference on Communications, 2007)
In the current Internet, compliance with TCP congestion control rules is voluntary. Noncompliant flows can gain unfair performance advantages or deny service to other flows. We propose a scheme that automatically detects and segregates noncompliant flows and preserves network availability for compliant flows. Our scheme requires modifications only in access routers and is incrementally deployable. Experiments demonstrate that our scheme is effective and has acceptable overhead.